2015
DOI: 10.1016/j.annepidem.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

A pooled multisite analysis of the effects of atopic medical conditions in glioma risk in different ethnic groups

Abstract: Background The incidences of atopic conditions (allergies, asthma or eczema) and glioma vary by ethnicity. Atopic conditions are inversely associated with gliomas. We conducted a pooled multi-site study investigating the associations of atopic conditions with glioma in different race/ethnicity groups. Methods Using glioma cases and healthy controls, unconditional logistic regression was conducted to assess the associations of atopic conditions with glioma separately in White, Black, Asian and Hispanic subpop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The mORs reported in our study for overall allergies and respiratory allergies fall within this range. Similarly, our effect estimates for asthma and eczema are also consistent with these and other smaller studies (14, 27, 28, 35). Based on the growing body of evidence in the literature, the scientific community may be approaching a consensus on the role of allergies in glioma risk (36, 37).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The mORs reported in our study for overall allergies and respiratory allergies fall within this range. Similarly, our effect estimates for asthma and eczema are also consistent with these and other smaller studies (14, 27, 28, 35). Based on the growing body of evidence in the literature, the scientific community may be approaching a consensus on the role of allergies in glioma risk (36, 37).…”
Section: Discussionsupporting
confidence: 92%
“…With some exceptions (810), the majority of studies have found that allergic conditions may reduce glioma risk by as much as 20–40% (14, 7). These associations have been examined using single- [i.e., (11)], multi-site [i.e., (1214)], and nested case-control studies [i.e., (15, 16)], prospective cohort studies [i.e., (3)], and meta-analyses [i.e., (1, 2, 7)]. Additionally, the observed inverse association between allergies and glioma has remained consistent across studies with different exposure assessment strategies, such as self-reported allergy status (3), self-reported physician-diagnosed allergies (12, 13, 1719), number of allergy types (12, 17), and allergy-related biomarkers, such as Immunoglobulin E [overall (4, 11, 16, 20), pre-diagnostic (16, 21), and/or allergen-specific (11, 15, 16)], soluble CD23 levels (22), and polymorphisms in allergy-related genes (2326).…”
Section: Introductionmentioning
confidence: 99%
“…PFS and OS between the two groups were not statistically distinct from one another. There are several studies that document the mutational statuses of GBM, with some demonstrating disparities in PFS and OS between races [ 23 25 26 28 32 33 35 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 ]. Dai et al [ 33 ] performed a meta-analysis of GBM patients which included studies from Europe, North America, and Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory authorities increasingly require subgroup analysis of data by ethnicity . The inverse association between glioma and atopic conditions reportedly varies with ethnicity, there being no association in the black population . Heath et al have recently reported significant differences and trends in molecular signatures of the three cancer types in African Americans and Caucasians, a finding that implies racial/ethnic differences in carcinogenesis and response to the drug being investigated.…”
Section: Challenges and Overcoming Obstaclesmentioning
confidence: 99%
“…221 The inverse association between glioma and atopic conditions reportedly varies with ethnicity, there being no association in the black population. 222 Heath et al 223 have recently reported significant differences and trends in molecular signatures of the three cancer types in African Americans and Caucasians, a finding that implies racial/ethnic differences in carcinogenesis and response to the drug being investigated. It has been reported that among diabetic men without metformin use, prostate cancer incidence was higher in Hispanics and African Americans than in non-Hispanic Whites.…”
mentioning
confidence: 99%